Acute angle plication of optic nerve glioma as a mechanism of rapidly progressive visual loss. (2nd January 2021) - Tooley, Andrea A.; Rasool, Nailyn; Campbell, Ashley; Kazim, Michael
ABSTRACT: Purpose : The majority of pediatric patients with optic nerve gliomas (ONG) remain asymptomatic; however, a subset of patients suffer rapid, irreversible visual loss. The purpose of this study was to determine anatomic differences of ONG noted either by imaging or by intra-operative observation between patients with gradual visual dysfunction and those with rapid visual loss. Methods : A retrospective review was performed in patients with visual loss secondary to ONG. The clinical records, pathology, and radiographic images were reviewed for all patients. The degree of folding or plication of the optic nerve (ON) was determined by analyzing the most acute angle present in the course of the ON. Outcome measures : The primary outcome measure was the angle of plication or folding of the ON and the relationship of this to the course of visual dysfunction. Results : Six patients with ONG were included in the study. A structural difference in the ON was identified in four patients with rapid vision loss compared with two patients with more gradual visual dysfunction. In patients with rapid progressive visual loss, the ONG had a 90-degree or more acute plication of the ON. Those with more gradual visual loss had more obtuse bends in the ONG. Conclusions : We have identified that the intrinsic structure of the ONG may contribute to the rare but devastatingly rapid progression of visual dysfunction in some patients. Recognizing these changes may guide clinicians to intervene prior to the development of irreversible visual loss.